Mutu Pelayanan Kesehatan Puskesmas Pasir Panjang Pasca Akreditasi - Lusia D. I. Fernandez; Yoseph Kenjam; Dominirsep O. Dodo (Media Kesehatan Masyarakat, 2021)
In order to maintain the quality of health services at the health center running maximally, it is necessary to improve performance and sustainable improvement. The Pasir Panjang Health Center has obtained the "Utama" accreditation status in 2018. After the Health Center is accredited, it is hoped that the quality of health services will improve. The purpose of this study was to determine the quality of health services at the Pasir Panjang Health Center after accreditation is implemented. This study used a quantitative method with a cross sectional survey design. The research sample consisted of 34 respondents who were selected by purposive sampling technique. The results of the study found that after accreditation, the quality of health services at Pasir Panjang Health Center obtained the following results: the dimensions of technical competence 83,29%, effectiveness, 82,64%, continuity 82,54%, security 82,64%, information 82,50%, accuracy time 78,23%, and human relations 82,11%. Seeing the results of this study, the Pasir Panjang Health Center must implement a sustainable quality management system to maintain the good quality of its services, including regulating the disciplinary behavior of health care workers, given that the dimension of timeliness received the lowest assessment from the respondents.